Reducing Groundwater Pollution through Increased Humus Content and Soil Sorptive Capacity Using Angren Coal Dust - Mavlyanov Gani Narimonovich (Scientific Trends, 2025)
This study explores an innovative approach to mitigating groundwater pollution caused by nitrate and nitrite leaching from agricultural soils. By applying coal dust—a by-product of the Angren coal industry—onto cotton and wheat fields, we observed enhanced sorption of nitrogen compounds and improved soil quality. Results demonstrate a significant reduction in nitrate content in groundwater, as well as increased humus content and soil water retention. This method provides a sustainable solution to both environmental pollution and soil degradation in arid agricultural regions.
Keywords: Coal dust, nitrates, nitrites, groundwater pollution, humus, Angren, soil absorption capacity.